The Wage Policy of Firms: Comparative Evidence for the U.S. and Germany from Personnel Data - Christian Grund (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
The wage policy of a German and a U.S. firm is comparatively analysed with a focus on the relation between wages and hierarchies. While prior studies examine only one particular firm, in this paper two plants of the same owners with similar production processes in different institutional environments are inspected. Convex wage profiles over the hierarchy levels of both plants are found. The U.S. plant shows considerably higher intensity of intra-firm competition in terms of higher intra-level wage inequality and yearly promotion rate. In contrast, wages are more distinctly attached to hierarchy levels in the German firm, as wage regressions show. The results are discussed in comparison to prior studies.
Keywords: M52; M12; J31; 330; Hierarchies; Intra-firm wages; Personnel records; Lohnstruktur; Vergütungssystem; Erwerbsverlauf; Hierarchie; Vergleich; Schätzung; Deutschland; Vereinigte Staaten